3.9k views
3 votes
Find p if x=-3 is a factor of 2x³- 2px² + p + 2



1 Answer

5 votes

Answer:

2x³- 2px² + p + 2

First plug in x = -3

2(-3)³- 2p(-3)² + p + 2

According to PEMDAS, we should solve the exponents first.

(-3)³ = -27

(-3)² = 9

2(-27) - 2(9)p + p + 2

Now multiply.

-54 - 18p + p + 2

Now combine the variables and constants.

-17p - 52

This is the simplified expression.

If it is an equation, then it would equal 0.

-17p - 52 = 0

To solve for p, add 52 to both sides.

-17p = 52

Now isolate the p by dividing by -17.

p = -52/17 or -3.0589

User Bongo
by
5.0k points